APPROACH TO THE DISTRIBUTION OF PARALLEL TASK THREADS IN COMPUTING SYSTEMS - Smetanin, R. I.; Tiagunova, M. U. (Radio Electronics, Computer Science, Control, 2012)
The problem of the tasks distribution in the computer system with different execution time of parallel threads, which must be distributed, is considered. Method to improve distribution efficiency is developed. Method is effective, because it much educes execution time of task.